Representasi Otoritarianisme dalam Cerita Rakyat Kutai Berjudul “Punang” - Anhar, Anhar; Rahman, Syafa Aulia; Septiani, Sasi (Indo-MathEdu Intellectuals Journal, 2024)
The aim of this study is to explore the representation of authoritarianism in the Kutai folklore titled Punang, focusing on both the intrinsic and extrinsic aspects of the text. Through this story, it becomes evident how power and customary laws influence the social life of the community, particularly the pressure faced by King Buy to marry in order to produce offspring. The study employs a qualitative descriptive method with a hermeneutic and narrative approach to reveal messages of authoritarianism within the story. The findings indicate the presence of cultural authoritarianism, as seen in how leaders are expected to submit to collective decisions and customary laws that regulate individual freedom. This research contributes to a deeper understanding of regional literature and demonstrates how traditional norms can shape power structures and social legitimacy within local communities.